Physiologic responses of comatose patients to liturgical text reading as a biobehavioral nursing intervention - Villamiel, Joseph Walter M.
The rising rate of accidents and lifestyle-related diseases that may lead to a comatose state, the advances in neurodiagnostic and treatment technologies vis-a-vis the emotional and economic burden on the family, and the bioethical dilemmas on clinical decisions are some reasons behind the growing concern for the comatose patients in the health care field. Despite such a concern, there remains a difficulty among nurses in operationalizing psychosociospiritual interventions for comatose patients, especially in ICU settings as much as they do physical care. Part of the hindrance to such a holistic care lies in questions regarding the actual sensory capability of these patients, the pertinent biobehavioral strategies that will address their psychospiritual needs, and the appropriate but feasible method of evaluating their responses. Inspired by these intensive care nursing concerns regarding comatose patients, this study was conducted to: (1) determined the significant physiologic responses of comatose patients to spiritual reading, particularly from liturgical texts, using blood pressure, heart rate, respiratory rate and overt motor movement as parameters; (2) to ascertain whether the physiologic responses of comatose patients to liturgical text reading, as manifested by the selected parameters, differ significantly from their corresponding physiologic response to non-liturgical text reading; and, (3) to identify some of the possible variables, pathophysiologic and sociodemographic, that may affect the comatose patients' physiologic responses to liturgical text reading. The study utilized a double-blind repeated measures experimental design and was conducted in selected intensive and special care units of a tertiary public hospital (UP-PGH). Complete enumeration of comatose patients confined within the 10-week period of data gathering and who met the 10-point subject inclusion criteria was implemented. This generated a sample size of 30, with the subjects equally but randomly assigned to the control and study (experimental) groups. The data collection methods included review of charts, interview of significant other/watcher, observation of motor responses, and measurement of physiologic response parameters. Subjects in the study group were given two types of auditory stimulus, liturgical (Psalms 23, 130 and 16) and non-liturgical (contemporary poetry) text readings. Both were tape-recorded in Filipino lasting 15 minutes per set, each one randomly administered to complete three morning and three evening sessions using a walkman cassette player with earphones and a pre-set fixed volume. The same schedule and audio equipment were given to the control group, but for them, blank tapes were played. A pilot-tested intervention protocol was followed, with the blinding approach applied by trained nurse research assistants to measure the physiologic response parameters and observe for motor movement, without knowing to what group did a subject belong and what particular record was being played. Physiologic responses were measured immediately prior to, at 10 minutes of, at the end of 15 minutes of, and at 15 minutes after the intervention. The results of the study showed that compared to the control group who did not receive any intervention, the study group exhibited more changes in parameter values during both liturgical and non-liturgical readings. However, for the study group, the change in parameter values during liturgical reading was greater than during non-liturgical reading. This was especially manifested by systolic and diastolic blood pressure mean values which tended to decrease more with liturgical readings than with non-liturgical reading sessions. This appears to denote a calming or relaxing effect brought about by both types of recorded reading interventions, but which was more apparent during the liturgical reading. The changes were less apparent for HR and RR.